Pentecostal Ecclesiology : An Essay on the Development of Doctrine - Chan, Simon K.H., (Journal of Pentecostal Theology Supplement Series, 2011)
This book argues that if the Pentecostal movement is to overcome its excessive individualism and structural instability the way forward is not more institutionalization but a coherent and robust ecclesiology based on the Pentecost event, which is the coming of the Holy Spirit in his own person into the church. A Pentecostal ecclesiology is essentially the working-out of the ramifications of that key event. The book takes a more ontological understanding of the relationship between the Spirit and the church than would Protestant and evangelical ecclesiologies. In this respect, it has more in common with Orthodoxy. It is further argued that this realignment away from Protestantism and evangelicalism towards Orthodoxy, far from removing Pentecostals from their roots, actually brings them much closer to the heart of Pentecostal spirituality.